Endocytosis and its regulation in plants. (June 2015) - Fan, Lusheng; Li, Ruili; Pan, Jianwei; Ding, Zhaojun; Lin, Jinxing
Highlights We review the clathrin-dependent and membrane microdomain-associated endocytic routes in plant cells. We describe the degradation of endocytosed proteins, ESCRT-mediated vesicle formation at the endosome. We summarize the essential roles of various regulators during plant endocytosis.